Maternal control of the fetal and neonatal rat suprachiasmatic nucleus - El-Hennamy, Rehab; Mateju, Kristyna; Bendová, Zdena; Sosniyenko, Serhiy; Sumová, Alena (Journal of biological rhythms, 2008)
The molecular clockwork underlying the generation of circadian rhythmicity within the suprachiasmatic nucleus (SCN) develops gradually during ontogenesis. The authors' previous work has shown that rhythms in clock gene expression in the rat SCN are not detectable at embryonic day (E) 19, start to form at E20 and develop further via increasing amplitude until postnatal day (P) 10. The aim of the present work was to elucidate whether and how swiftly the immature fetal and neonatal molecular SCN clocks can be reset by maternal cues. Pregnant rats maintained under a light-dark (LD) regimen with 12 h of light and 12 h of darkness were exposed to a 6-h delay of the dark period and released into constant darkness at different stages of the fetal SCN development. Adult rats maintained under the same LD regimen were exposed to an identical shifting procedure. Daily rhythms in spontaneous c-fos, Avp, Per1, and Per2 expression were examined within the adult and newborn SCN by in situ hybridization. Exposure of adult rats to the shifting procedure induced a significant phase delay of locomotor activity within 3 days after the phase shift as well as a delay in the rhythms of c-fos and Avp expression within 3 days and Per1 and Per2 expression within 5 days. Exposure of pregnant rats to the shifting procedure at E18, but not at E20, delayed the rhythm in c-fos and Avp expression in the SCN of newborn pups at P0-1. The shifting procedure at E20 did, however, induce a phase delay of Per1 and Per2 expression rhythms at P3 and P6. Hence, 5 days were necessary for phase-shifting the pups' SCN clock by maternal cues, be it the interval between E18 and P0-1 or the interval between E20 and P3, while only 3 days were necessary for phase-shifting the maternal SCN by photic cues. These results demonstrate that the SCN clock is capable of significant phase shifts at fetal developmental stages when no or very faint molecular oscillations can be detected.
Keywords: cirkadiánní proteiny Period; hybridizace in situ; Animals, Newborn; Male; vývojová regulace genové exprese; Gene Expression Regulation, Developmental; Oscillometry; Mothers; In Situ Hybridization; jaderné proteiny; Arginine Vasopressin; mužské pohlaví; Suprachiasmatic Nucleus; arginin vasopresin; novorozená zvířata; Models, Biological; lokomoce; proteiny buněčného cyklu; krysa rodu Rattus; Animals; Locomotion; biologické modely; ženské pohlaví; nucleus suprachiasmaticus; oscilometrie; Period Circadian Proteins; zvířata; Rats; protoonkogenní proteiny c-fos; Female; Cell Cycle Proteins; Nuclear Proteins; matky; Proto-Oncogene Proteins c-fos